2022
DOI: 10.14236/ewic/hci2022.30
|View full text |Cite
|
Sign up to set email alerts
|

Do People Matter? Presence and Prosocial Decision-making in Virtual Reality

Abstract: Virtual reality (VR) simulations with virtual characters have been increasingly deployed to understand context-based human behaviour. The current study investigated the effects of perceived agency of the other players, who were either (human-controlled) avatars or (computer-controlled) agents, on the player's overall presence levels (with 3 subscales of spatial presence, involvement, and realism). We also tested the relationship between the player's perception of the agency of the other players, in-game prosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Participants who embodied the ability to fly showed better helping behaviour, which facilitated subsequent helping behaviours in the real world (Rosenberg et al, 2013). On the other hand (Wei and Bramwell-Dicks, 2022), demonstrated that people's virtual behaviours are influenced by their personality traits and the perceived agency of the other players. Given the different embodiment of the VCs used, as discussed above, it is difficult to compare the results observed.…”
Section: Types and Effects Of Prosocial Behaviour (Rq3)mentioning
confidence: 95%
See 4 more Smart Citations
“…Participants who embodied the ability to fly showed better helping behaviour, which facilitated subsequent helping behaviours in the real world (Rosenberg et al, 2013). On the other hand (Wei and Bramwell-Dicks, 2022), demonstrated that people's virtual behaviours are influenced by their personality traits and the perceived agency of the other players. Given the different embodiment of the VCs used, as discussed above, it is difficult to compare the results observed.…”
Section: Types and Effects Of Prosocial Behaviour (Rq3)mentioning
confidence: 95%
“…While the observed context-sensitivity of prosocial behaviours poses challenges for the creation of a unified theoretical framework, this also opens new questions for future research as it highlights the dynamic interplay between situational factors and prosocial actions. Recognising the influence of individual traits and environmental factors, as research suggests (Davis et al, 1999;Wei and Bramwell-Dicks, 2022), we can now envision interactive environments and EVAs tailored to guide and nudge individuals toward prosocial choices. This aligns with findings that spontaneous cooperation is more likely in individuals with a prosocial orientation (Mischkowski and Glöckner, 2016), suggesting that by shaping the interactive environment, prosocial inclinations can be encouraged (Brian, 1999).…”
Section: The Role Of Prosociality In Human-agent Interaction In Xrmentioning
confidence: 99%
See 3 more Smart Citations